A retrospective clinical, multi-center cross-sectional study to assess the severity and sequela of Noma/Cancrum oris in Ethiopia. - Heron Gezahegn Gebretsadik; Laurent Cleenewerck de Kiev (Public Library of Science (PLoS), 2022)
Introduction Noma is a disfiguring gangrenous disease of the orofacial tissue and predominantly affects malnourished children. The tissue gangrene or necrosis starts in the mouth and eventually spreads intra-orally with the destruction of soft and hard tissues. If not controlled, the natural course of the condition leads to a perforation through the skin of the face, creating a severe cosmetic and functional defect, which often affects the mid-facial structures. Furthermore, the course of the disease is fulminating, and without timely intervention, it is fatal. Materials and methods A retrospective clinical cross-sectional study was conducted to assess the sequela and severity of Noma in Ethiopia. Medical records of patients diagnosed with Noma were reviewed. The medical files were obtained from Yekatik 12 Hospital, Facing Africa, and the Harar project,-the three major Noma treatment centers in Ethiopia. The severity of facial tissue damage and the extent of mouth trismus (ankylosis) were examined based on the NOIPTUS score. Results A total of 163 medical records were reviewed. Of those, 52% (n = 85) and 48% (n = 78) have reported left-sided and right-sided facial defects, respectively. The facial defects ranged from minor to severe tissue damage. In other words, 42.3% (n = 69), 30.7% (n = 50), 19% (n = 31), and 8% (n = 13) have reported Grade-2 (25-50%), Grade-3 (50-75%), Grade-1 (0-25%), and Grade-4 (75-100%) tissue damages respectively. Cheek, upper lip, lower lip, nose, hard palate, maxilla, oral commissure, zygoma, infra-orbital region, mandible, and chin are oftentimes the major facial anatomic regions affected by the disease in the individuals identified in our review. Complete loss of upper lip, lower lip, and nose were also identified as a sequela of Noma. Discussion The mortality rate of Noma is reported to vary between 85% and 90%. The few survivors suffer from disfigurement and functional impairment affecting speech, breathing, mastication, and/or even leading to changes in vision. Often, the aesthetic damage becomes a source of stigma, leading to isolation from society, as well as one's family. Similarly, our review found a high level of facial tissue damage and psychiatric morbidity.